Cash flows and financial performance in the industrial sector of Saudi Arabia: With special reference to Insurance and Manufacturing Sectors - Abdul Rahman (Investment Management & Financial Innovations, 2020)
A firm with proper cash flow management can increase its financial performance, while improper management might lead to financial failure. Therefore, it is significant for a firm to manage cash inflows and outflows properly. The current study investigates the effect of cash flow from operations (CFOs) on the financial performance of insurance and manufacturing companies in Saudi Arabia. The data were extracted from companies’ annual reports by considering Return on Assets (ROA) and Return on Equity (ROE) as dependent variables, CFOs as an explanatory variable, firm size (SIZE) and Leverage (LEV) as control variables, and an industry dummy. The results report a positive and significant association between financial performance (ROA and ROE) and operating cash flows (CFOs), and a negative association for SIZE and LEV. Therefore, the study concludes that the firms’ operating cash flows in the insurance and manufacturing sectors in Saudi Arabia affect financial performance.